Keamanan Data dalam Penggunaan IoT untuk Menghimpun dan Mengelola Big Data - syahla, Syahla Nadya Putri Syabrina (Jurnal Informatika & Teknologi Cerdas, 2025)
In the era of rapid information system growth, the utilization of the Internet of Things (IoT) and Big Data has become a primary focus for modern companies. IoT devices, which are connected to the internet, play a crucial role in collecting, transmitting, and processing data from various sources. Meanwhile, Big Data describes large and diverse datasets that, if properly leveraged, can provide numerous benefits. However, with the increasing use of IoT and Big Data, the protection of information security becomes increasingly important. The aim of this study is to analyze the main challenges in data security related to the use of IoT for managing Big Data. The research method involves a literature review of various relevant national and international journal articles. The results indicate that the main challenges include extensive data collection, data security, individual identification, user control, and third-party data access. Therefore, a balanced integration of IoT technology, Big Data, and data security practices is key to ensuring business success and sustainability in this digital era.